CTL14, a recognition receptor induced in late stage larvae, modulates anti-fungal immunity in cotton bollworm Helicoverpa armigera. (July 2018) - Cheng, Yang; Lin, Zhe; Wang, Ju-Mei; Xing, Long-Sheng; Xiong, Guang-Hua; Zou, Zhen
Abstract: C-type lectin (CTL) is usually considered as pattern recognition receptors in insect innate immunity. Here we found that CTL14 of Helicoverpa armigera was only activated in the fifth instar larvae not in the second instar by entomopathogen Beauveria bassiana infection. Recombinant CTL14 protein was found to form aggregates with zymosan and B. bassiana in vitro . Immunoprecipitation studies demonstrated that CTL14 interacted with serine proteinases (SP), serine proteinase inhibitor (serpin), prophenoloxidases (PPO) and vitellogenin (Vg) in the larval hemolymph. Furthermore, depletion of CTL14 using dsRNA led to dramatic decrease in the expression level of PPO1. Additionally, CTL14 depleted H. armigera decreased the resistance to fungal challenge. Taken together, our study showed the direct involvement of CTL14 in the anti-fungal immunity of H. armigera, which further explained the stronger immune responses in the fifth instar compared to the second instar larvae. Highlights: CTL14 is induced by fungi in the fifth instar larvae, not in the second instar. Recombinant CTL14 is able to bind and agglutinate Beauveria bassiana. CTL14 modulates the expression of SPs and serpin to regulate melanization pathway. CTL14-rich hemocytes are capable of phagocytosing fungal conidia.